Agricultural Techniques Utilizing Implementation of Renewable Energy (International Journal of Innovative Research in Engineering & Management, 2021)
Agricultural practises in poor nations are typically done by  hand using blunt instruments, while fossil fuel use in wealthy  countries has resulted in significant global warming and  environmental damage. The objective of the research was to  establish how much renewable energy is utilized in  agricultural activities, as well as its limits and potential  remedies. Renewable energy source explored include biomass,  geothermal, wind, sun, hydropower, and fuelwood.  Sustainable energy farming in agriculture to limit the quantity  of carbon emitted into the environment by converting fossil  fuel burning to renewable energy sources. Agriculturalists  produces capital worldwide input and integrating them with  energy-saving methods. Green energy lets companies save  cash while simultaneously combating the effects of global  warming. Wind, hydropower as well as solar electricity, plus  biomass are examples of potential renewable energy sources  for the rural agricultural industry. They may be utilized to  decrease the energy gap in rural as well as metropolitan region  while simultaneously reducing the pace of environmental  degradation. In order to produce, manage, monitor, and  evaluate renewable energy, sufficient is needed to educate and  transmit this information to rural region. The rising need for  food, combined with the fluctuating charge on fossil fuel, has  driven a hunt for ecologically acceptable energy sources.  Energy is a significant cost in the production management.  The use of a sustainable energy grid to monitor green-house  environment reduces consumption of fuel plus improves the  sustainability of green-house building.
Keywords: Agriculture; Biomass; Clean Energy; Geothermal; Hydropower; Renewable Energy